A Case of Extranodal NK/T-cell Lymphoma in Which a Diagnosis Was Difficult to Make - Asano, Toshiaki; Ogawa, Maiko; Tanaka, Taro; Machii, Haruka; Shima, Koichiro; Ieda, Miho; Iwama, Mayuko; Ito, Toshiyasu; Imamura, Taeko; Nishio, Tomoko (The Journal of the Japan Society for Respiratory Endoscopy, 2023)
Background. Extranodal NK/T-cell lymphoma, nasal type (ENKL) presenting with lung involvement is rare and often difficult to diagnose. Case. We encountered a 61-year-old man who had been suffering from back pain for one month before his first visit. Computed tomography revealed mass lesions in the right upper and lower lobes, as well as enlarged mediastinal lymph nodes. Bronchoscopy was conducted twice, but no diagnosis was made. Because of the accumulation of 18F-fluorodeoxyglucose positron emission tomography in the rectum, colonoscopy was conducted. A rectal tumor was found and biopsied, but it could not be differentiated as inflammation or malignancy. One month later, the right cervical lymph node was found to be enlarged. A biopsy revealed malignant lymphoma. The patient was finally diagnosed with ENKL. Chemotherapy was administered, but the patient died eight months after the initial diagnosis due to worsening of the primary disease. Conclusion. When necrotic tissue is evident on a biopsy, clinicians should always consider ENKL. For an early definitive diagnosis, it is important to increase the number of biopsies performed.